2018
DOI: 10.1007/s00726-018-2559-x
|View full text |Cite
|
Sign up to set email alerts
|

l-Cysteine in vitro can restore cellular glutathione and inhibits the expression of cell adhesion molecules in G6PD-deficient monocytes

Abstract: L-Cysteine is a precursor of glutathione (GSH), a potent physiological antioxidant. Excess glucose-6-phosphate dehydrogenase (G6PD) deficiency in African Americans and low levels of L-cysteine diet in Hispanics can contributes to GSH deficiency and oxidative stress. Oxidative stress and monocyte adhesion was considered to be an initial event in the progression of vascular dysfunction and atherosclerosis. However, no previous study has investigated the contribution of GSH/G6PD deficiency to the expression of mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 31 publications
(15 citation statements)
references
References 60 publications
1
14
0
Order By: Relevance
“…The NO values obtained in the study were in line with published findings utilizing unstimulated and LPS-activated U937 cells ( 50 52 ). Monocytic cells exhibited a substantial (more than 1.5-fold) concentration-dependent increase ( P < 0.05) in NO and iNOS production when treated with mCRP (Figures 4 A and 5 A), regardless of their activation state.…”
Section: Resultssupporting
confidence: 90%
“…The NO values obtained in the study were in line with published findings utilizing unstimulated and LPS-activated U937 cells ( 50 52 ). Monocytic cells exhibited a substantial (more than 1.5-fold) concentration-dependent increase ( P < 0.05) in NO and iNOS production when treated with mCRP (Figures 4 A and 5 A), regardless of their activation state.…”
Section: Resultssupporting
confidence: 90%
“…A cell-based experiment partly revealed the mechanism with which EGCG inhibits 3T3-L1 preadipocyte differentiation, activates AMPK, and decreases fat accumulation [ 28 ]. GTCs could also have protective effects on endothelial cells as other antioxidants do, by inhibiting the adhesion of monocytes [ 29 , 30 ]. In another cell-based study, EGCG was shown to suppress the mRNA expression of monocyte chemotactic protein-1, which accelerates the progress of atherosclerosis by promoting the adhesion of monocytes [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…The endothelium was partially protected from monocytic cell adhesion by pretreatment with L-cysteine ethyl ester (cell-permeable) ( Figure S2 ). Hence, it is possible that G6PD deficiency-induced cellular dysfunctions could be prevented by supplementation with the micronutrient L-cysteine, which directly boosts the levels of the major antioxidant GSH and increases the transcription of G6PD [ 32 , 33 , 34 , 35 ], because G6PD deficiency increases oxidative stress and adversely affects the endothelium by activating TGF-β/Smad/NOX components. Future studies are needed to investigate whether supplementation with L-cysteine can be beneficial to the G6PD-deficient population.…”
Section: Discussionmentioning
confidence: 99%
“…The diluted siRNA was combined with diluted lipofectamine, followed by an additional incubation at room temperature for 30 min to allow siRNA complexes to form before addition to the cells. Cells were incubated with siRNA medium for 4 h at 37 °C, followed by incubation with complete fresh media for the next 24 h. The double-stranded control siRNA-A (Santa Cruz Biotechnology, sc-37007) does not match any other current sequences used as a control in the experiments [ 34 , 35 , 40 ]. After the transfection procedure, G6PD-deficient cells were treated with basal medium at different time points, similar to the treatment protocol described elsewhere in this paper.…”
Section: Methodsmentioning
confidence: 99%